Ecosse, littérature et nationalisme culturel : le phantasme d’une nation ? - Camille Manfredi (Amnis)
When, in June 1999, the first Scottish parliament since 1707 was restored, it was anything but a small event. A quick inspection of Scottish society tends to prove that although Scotland had been part of a highly centralised state for nearly three centuries, the sense of a distinct national identity has survived, despite a rather chaotic history of political frustration and largely self-sustained oppression. This article offers to deal with nationalism in terms of discursive strategies designed to forge the community’s self-identity and of an ideological and mainly literary quest for self-definition. It will thus reveal a plethora of (mis)representations of Scotland throughout the centuries, a profusion of ‘imagined communities’ and idealised versions of national history and fables that have so far failed to successfully epitomise a nation which is still struggling against enduring dilemmas to design its own image.